Comparative analysis of the male reproductive accessory glands of bat species from the five Brazilian subfamilies of the family Phyllostomidae (Chiroptera) - Martins, Fabiane F. [UNESP]; Puga, Cintia C. I. [UNESP]; Beguelini, Mateus R. [UNESP]; Morielle-Versute, Eliana [UNESP]; Vilamaior, Patricia S. L. [UNESP]; Taboga, Sebastiao Roberto [UNESP] (Wiley-Blackwell, 2015)
This study aimed to morphologically characterize and compare the male reproductive accessory glands (RAGs) of bats belonging to the five Brazilian subfamilies of the family Phyllostomidae (Carollia perspicillata—Carollinae; Desmodus rotundus—Desmodontinae; Glossophaga soricina—Glossophaginae; Phyllostomus discolor—Phyllostominae and Platyrrhinus lineatus—Stenodermatinae). The study demonstrated that the RAGs of phyllostomid bats were comprised of a pair of extra-abdominal bulbourethral glands and an intra-abdominal complex, composed of paraurethral glands and a prostate with two (Desmodontinae and Stenodermatinae) or three (Carollinae, Glossophaginae and Phyllostominae) different regions, with the absence of the seminal vesicles; this pattern possibly evolved from a process of compaction of the prostatic regions from an ancestor with three regions.
Keywords: Prostate; Evolution; Bulbourethral gland; Paraurethral gland